Has the Adaptation‐Mitigation Binary Outlived Its Value? Indigenous Ways of Knowing Present an Alternative. Issue 2 (30th June 2022) - Ullmann, Anna L.; Kassam, Karim‐Aly S.
Abstract: Community‐level actions addressing anthropogenic climate change are paramount to survival. However, there are limitations to the current binary approach which considers adaptation and mitigation as mutually exclusive actions. Drawing from research in the Pamir Mountains of Tajikistan, this commentary demonstrates: (a) Indigenous knowledge, emerging from a deep connectivity to habitat, cumulative over generations, and empirically‐based, is the foundation of ecological calendars; (b) ecological calendars build anticipatory capacity, the ability to envision possible and sustainable futures, for anthropogenic climate change; and (c) this anticipatory approach engages adaptive and mitigative actions to climate change working in tandem to ensure wellbeing and food security. This paper maintains that the adaptation‐mitigation continuum involves foresight and action today in preparation for future change. Furthermore, context‐specific ecological calendars represent an effective mechanism for communities to build and retain knowledge across generations and deep connections to their habitat. Finally, further modeling needs to be undertaken with participation and leadership from Indigenous and rural communities to understand how they use the adaptation‐mitigation continuum for anticipatory action to develop multiple optimal solutions to address environmental change. Plain Language Summary: Adaptation and mitigation are related components of anticipatory capacity which informs a community's action to secure its livelihood and food systems. Anticipatory capacity, the ability to envision sustainable futures under conditions of anthropogenic climate change, needs to be grounded in the local ecological and sociocultural context to be effective. It relies on various ways of knowing, that consider the complex connectivity of relations between humans and their habitat within a specific context. In this reflective essay, a strong case is made for Indigenous knowledge systems as providing a foundational base for strategic action to the climate crisis while also engaging complementary knowledge sources from the biophysical and social sciences. This grounded and "thick" understanding can be brought to bear on actions that simultaneously mitigate and adapt to anthropogenic climate change. In an upcoming special issue of GeoHealth entitled "Rhythms of the Earth: Ecological Calendars and Anticipating the Anthropogenic Climate Crisis, " international research will be presented to demonstrate, in diverse international Indigenous contexts, a culturally and ecologically grounded approach to addressing the local level impacts of anthropogenic climate change. Key Points: The adaptation‐mitigation binary, while conceptually useful, does not reflect how rural societies make decisions about climate change Anticipatory capacity includes facets of adaptation and mitigation strategies working in tandem rather than as mutually exclusive decisions For generations, Indigenous communities have used ecological calendars as a form of anticipatory capacity for seasonal and climatic changes